Civil Conflict and Firm Performance : Evidence from Cote d'Ivoire - Klapper, Leora; Richmond, Christine; Tran, Trang (World Bank, Washington, DC, 2014)
This paper investigates the impact of political instability and civil conflict on firms. It studies the unrest in Cote d'Ivoire that began in 2000, using a census of all registered firms for the years 1998-2003. The analysis uses structural estimates of the production function and exploits spatial variations in conflict intensity to derive the cost of conflict on firms in terms of productivity loss. The results indicate that the conflict led to an average 16-23 percent drop in firm total factor productivity and the decline is 5-10 percentage points larger for firms that are owned by or employing foreigners. These results are consistent with anecdotal evidence of increasing violent attacks and looting of foreigners and their businesses during the conflict. The results suggest increases in operating costs is a possible channel driving this impact. Finally, the paper investigates whether firms responded by hiring fewer foreign workers and finds evidence supporting this hypothesis.